Sisters of Solidarity - Yates, Charlotte A. B. (Charlotte Alyce Bronwen) (Labour / Le Travail, 1994)
The article reviews the book, "Sisters of Solidarity," by Julie White.
Keywords: BOOKS – Reviews; Nonfiction; SISTERS of Solidarity (Book); WHITE; Julie; Women